Shopping and Word-of-Mouth Intentions on Social Media - Patrick Mikalef (Journal of Theoretical and Applied Electronic Commerce Research, 2013)
Social Media has been gaining popularity worldwide over the last years at an increasingly growing rate. Motivated by this fact, firms are piloting different approaches of promoting their products and services to consumers in order to capitalize on the prominence of such websites. However, there is much debate in the academic and business community about the potential of social media as a platform for marketing and commerce, and the viable strategies that could constitute them as a possible solution for future ventures. Research to date has been growing, with only a limited number of studies exploring the business potential of social media. The aim of this research is to elucidate how specific aspects of social media websites foster user intention to browse products, and the effect that this has in shaping purchasing and information sharing intentions. Utilitarian and Hedonic motivation theory provides the theoretical background on which we segregate the factors that contribute to product browsing on social media websites. Partial Least Squares (PLS) analysis is performed on data obtained from 165 social media users to test our research model. Outcomes indicate that specific aspects trigger Utilitarian (Convenience and Product Selection) and Hedonic (Idea and Adventure) motivations which in sequence impact user intention to browse products on such mediums. Finally, browsing intention is linked in a significantly positive manner with purchasing and word-of-mouth intention.